LEXICAL SIMILARITY LEVEL BETWEEN ENGLISH AND PORTUGUESE - Maldonado García, Maria Isabel; Borges de Souza, Ana Maria (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract Although the studies which calculate the similarity index between languages are abundant, to date the similarity index between English and Portuguese has not been calculated. When calculating the similarity index between English and Portuguese it is important to have in consideration the amount of Latin loan words English has received from Latin which may influence the similarity index. However, English is a Germanic language whereas Portuguese is a Romance language. The purpose of this research is to calculate this level of lexical similarity through the computational lexical distance comparison of 500 high frequency words in English and Portuguese and the identification of cognates. The main hypothesis of this study is based on the fact that English and Portuguese degree of genetic difference may be less than 30% considering that the comparison of English with other Romance languages has resulted in similar indexes. The study is aimed at assisting students of English or Portuguese as an L2 with their language acquisition through the identification of items which present similarities in both languages and in this manner aid vocabulary acquisition. Resumen Se han realizado múltiples estudios para revelar el nivel de similitud entre diferentes lenguas. Sin embargo, el nivel de similitud entre el inglés y el portugués no se ha calculado todavía. El inglés ha recibido una considerable cantidad de préstamos del latín, lo cual puede aumentar el nivel de similitud entre las dos lenguas debido a que el portugués deriva directamente del latín. Sin embargo, el inglés es una lengua germánica, mientras que el portugués es una lengua romance. El propósito de esta investigación es calcular este nivel de similitud léxica a través de la comparación de la distancia computacional léxica de 500 palabras de alta frecuencia del inglés y portugués y la identificación de cognados. La principal hipótesis de este estudio se basa en el hecho de que el inglés y el portugués presentan cierto grado de diferencia genética, y como tal, su coeficiente de similitud probablemente será inferior al 30%. El estudio tiene como objetivo ayudar a los estudiantes de inglés o portugués como L2 en la adquisición de la lengua a través de la identificación de elementos que presentan similitud en ambas lenguas.